2001
DOI: 10.1023/a:1008338312647
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase III study of early versus delayed whole brain radiotherapy with concurrent cisplatin and vinorelbine combination in inoperable brain metastasis of non-small-cell lung cancer: Groupe Français de Pneumo-Cancérologie (GFPC) Protocol 95-1

Abstract: These results confirm the efficacy of chemotherapy in brain metastases of NSCLC and suggest that the timing (early or delayed) of WBRT did not influence survival of NSCLC with brain metastasis treated with concurrent chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(133 citation statements)
references
References 27 publications
7
120
0
6
Order By: Relevance
“…Although most of the studies pointed out an improvement in local control compared with WBRT, the median survival times did not differ (Postmus et al, 2000;Robinet et al, 2001;Ushio et al, 1991Mornex et al, 2003.…”
mentioning
confidence: 97%
“…Although most of the studies pointed out an improvement in local control compared with WBRT, the median survival times did not differ (Postmus et al, 2000;Robinet et al, 2001;Ushio et al, 1991Mornex et al, 2003.…”
mentioning
confidence: 97%
“…The role of chemotherapy in patients with BrM by NSCLC is still controversial. However, among patients with NSCLC and BrM, response to different chemotherapy regimens, such cisplatin-gemcitabine or cisplatin-ifosfamide-irinotecan, was similar to that achieved in other disease sites [3][4][5][6][7][8][9]. Instead, for patients with recurrent or persistent BrM after WBRT and at least one line of chemotherapy, the treatment options available are limited.…”
Section: Discussionmentioning
confidence: 96%
“…Whole brain radiotherapy (WBRT) improves neurological symptoms in about 50% of patients and lengthens the median survival from 3 to 6 months [2]. Recent trials suggest that epipodophillotoxins alone or combined with cisplatin are very effective in treating NSCLCrelated BrM and ifosfamide-mitomycin-cisplatin or gemcitabine-cisplatin combinations have been evaluated with similar good responses [3][4][5][6][7][8][9]. Temozolomide (TMZ) is a novel, oral, alkylating agent with virtually 100% bioavailability [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult for chemical agents to reach the intracranial lesions due to the presence of blood-brain barrier, which limits the application of chemotherapy for patients with BM. Many recent studies showed that the BBB is damaged in patients with BM (Robinet et al, 2001;Grimm, 2012). Damaged BBB allows many chemotherapy drugs to penetrate into the intracranial lesion, thus improving the efficacy of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%